The reception of the Code of Canon Law of 1917 in Poland in the inter-war period - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2018)
Promulgation of the Code of Canon Law in 1917 by Benedict XV through a bull was a proud moment in the history of the legislation of the Latin Church. This formal collection of laws, which is a synthesis of legislative output of the Church of nineteen centuries, met with a lot of appreciation. The entry into force of the Code of Canon Law (19 of May 1918) was a demanding task for local Churches operating in particular countries, inter alia for the Church in Poland. This included not only a thorough study of the regulations of the Code, especially by bishops, but also a necessity to adapt then existing particular law to these regulations. Therefore, the reception of the Code of Canon Law in particular Churches became necessary. Assimilation of code standards by particular Churches, mainly through synods, took place in the context of increased activity of both a doctrine and centers in which canon law was taught. That is why when showing the process of reception of the Code of Canon Law in Poland in the above mentioned period (1918-1939), the author discusses its course in three fundamental areas in which it took place: in the canon doctrine (textbooks and comments to the Code of Canon Law), in the teaching of canon law (at universities and theological seminaries) and in particular Churches (with an example of Płock diocese).